Function Intelligence The District Attorney's Office in Revealing Action Criminal Corruption - Qalbi, Nurul; Qamar, Nurul; Assaad, Andi Istiqlal (Faculty of Law, Universitas Muslim Indonesia, 2025)
This study aims to analyze the role and function of the Pinrang District Prosecutor's Intelligence in disclosing criminal acts of corruption and identifying the obstacles faced in this process. The approach used is an empirical approach with data collection methods through interviews and literature study. Interviews were conducted with the Head of the Intelligence Section, members of the Intel Prosecutor, as well as practicing legal advocates who have in-depth knowledge and understanding regarding the disclosure of criminal acts of corruption and the legal processes that apply in Indonesia. The literature study was carried out by studying relevant laws and regulations as well as other scientific works that discuss the role of the District Attorney's intelligence in disclosing criminal acts of corruption. The research results show that the disclosure process begins with public reports or internal findings received and continues with data collection and exposure involving the Head of the District Attorney's Office, Head of the Intelligence Section, and Head of the Special Crimes Section to determine the feasibility of the investigation. Obstacles faced include limited budget, facilities, and external pressure from certain parties. Therefore, it is necessary to increase the budget and supporting facilities as well as protection for investigators so that the law enforcement process runs optimally. To increase the effectiveness of disclosing corruption cases, it is recommended that there be an additional budget, facilitation of a team of experts, better coordination between institutions, as well as increased transparency and education for the public. The prosecutor's office is also expected to increase the training and capacity of officers to overcome challenges in disclosing criminal acts of corruption in accordance with applicable legal procedures.